Colour constancy feature detection and matching technique for WLAN/Camera indoor positioning system - Wan Bejuri, Wan Mohd. Ya'akob (2013)
The location determination system in a changing environment, especially in an indoor environment can be very challenging if Global Positioning System (GPS) signals are blocked. It is necessary to combine or integrate multiple sensors and positioning methods in order to provide better location determination service to detect these signals. One of the most common platforms for this service is mobile phone technology which uses Wireless Local Area Network (WLAN) and camera. These positioning technologies allow determination of positioning information but the approach to the integration of WLAN and camera positioning feature detection and matching suffers from the illumination environment in the hallways of building. In this study, a positioning technique of colour constancy feature detection and matching for WLAN/Camera positioning was designed using colour constancy feature detection and matching to improve location determination in the illumination environment. The results showed the proposed design provides better location determination in the illumination environment (difference of no solution averaging: 12.9%) than Harlan Hile’s method. This research has proven that the proposed design will significantly contribute to the modernization of a location determination system.